The Effect Of Warm And Cold Compress Therapy As A Pain Distraction In The Elderly With Joint Pain At Wisma Tulip Upt Pstw Tulungagung - Brigita Putri Febrianti (Universitas STRADA Indonesia, 2026)
Joint pain is a common problem among the elderly, which can reduce quality of life and limit daily activities. Non-pharmacological interventions, such as warm and cold compress therapy, are often used to alleviate discomfort in older adults. The effectiveness of compress therapy is influenced by the type of pain, joint condition, and individual preferences, making it important to study the effect of both warm and cold compresses as pain distraction interventions. This study aimed to determine the effect of warm and cold compress therapy as a pain distraction on joint pain intensity in elderly residents at Wisma Tulip UPT PSTW Tulungagung and to identify the elderly’s preferences for the type of compress therapy. A one group pretest–posttest quasi-experimental design was used with 10 elderly participants experiencing joint pain. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the administration of warm and cold compresses. Data were analyzed descriptively, and the Wilcoxon Signed Rank Test was used to assess differences in pretest and posttest pain scores. Results: Both warm and cold compress therapies were effective in reducing joint pain. Cold compress therapy resulted in a more significant reduction in pain compared to warm compress therapy. Most respondents (70%) preferred cold compresses due to the rapid pain relief and comfort they provided, while 30% preferred warm compresses for muscle relaxation. Statistical analysis confirmed that cold compress therapy produced a more clinically meaningful decrease in pain scores than warm compress therapy. Conclusion: Warm and cold compresses are effective as pain distraction interventions for elderly individuals with joint pain, but cold compresses are more effective and preferred. The choice of therapy should be tailored to the type of pain and individual preferences to enhance comfort and improve the quality of life of the elderly.